Pengaruh Motivational Interviewing terhadap Tahap Perubahan Perilaku Klien Rehabilitasi Narkoba di Loka Rehabilitasi BNN Batam - Ranal, Acep (REAL in Nursing Journal, 2023)
Background: Drug abuse causes physical and psychological problems that cause various changes in the abuser with changes in maladaptive behavior. The National Narcotics Board shows that narcotics abuse in Indonesia is the largest in the Asian level because it uses 65 types of narcotics. In the preliminary study, it was found that there were 55 inpatients at the Batam BNN Rehabilitation Center. This study aims to determine the behavior stages of change before and after the application of Motivational Interviewing (MI) and to analyze its effect on drug rehabilitation clients. Methods: The research method is a quasi-experimental design with a one group pretest - posttest design approach without a control group. The sample consisted of 25 experimental group respondents who underwent inpatient rehabilitation at the Batam Rehabilitation Center of National Narcotics Board in 2022 with a sampling technique that was purposive sampling and the data was processed using the Wilcoxon test. Results: Univariate analysis of the results of the examination after being given MI showed 100% in the action stage. Bivariate results show that there is an effect of MI on the behavior stages of change with the difference in the mean before and after MI is 2.13 and P-Value 0.000 (<0.05).Conclusion:  It was concluded that there was an effect of MI on increasing the behavior stages of change in drug rehabilitation clients. It is recommended for nurses to apply the MI method in carrying out their role as counselors to increase the stage of changing the client's adaptive behaviorKeywords: Motivational Interviewing, Behaviour, Narcotics